(untitled) (Revista Archai, 2020)
The present study is an analysis of Plato’s Timaeus-Critias composition process, from the point of view of discourse modeling. It intends to show that the dialogue is distinguished by an insightful articulation of composition techniques, which combine the pictorial and dramatic aspects of poetic mimesis. Establishing the Panateneias as an implicit reference, the work presents the performance of a sequence of narratives, produced as true discursive images. Platonic originality is revealed in Timaeus-Critias, therefore, as the accomplishment of a formal construction that is both dramatic and representational, through a singular mimetic agency of discursive forms.